Thread kotiautomaatiossa - Parkkila, Jarmo Heikki Tapani (2024)
With the rapid growth of IoT, home automation is used in more and more homes today. Home automation is usually used to optimize resource usage, to make living more easier, comfortable and safer and also to save money and time. When utilizing home automation, a major technological challenge arises since devices and applications from different manufacturers are rarely compatible with each other. Because of this, integrating devices from different manufacturers to a single home automation platform is challenging, if not impossible and leads to use of multiple IoT platforms, ecosystems and applications in home. To tackle these compatibility issues between manufacturers, new technologies have been developed such as Matter and Thread. The purpose of this thesis is to give an overview of Thread as a technology. The thesis also aims to identify the most common challenges related to home automation and find out how these challenges could be avoided when setting up a home automation system. The beginning of the thesis focuses on covering opportunities and challenges related to home automation as well as the most common short-range wireless technologies used in home automation. Theoretical part ends with a technological study of Thread, which concludes with a short introduction to Matter. The empirical part of the thesis involves setting up a small-scale home automation system built on top of Home Assistant. The home automation system implemented in this thesis demonstrated, that the most significant challenges related to home automation can be avoided when utilizing open source IoT platform, appropriate IEEE 802.15.4 radio device and still relatively new technologies in home automation Matter and Thread.